Immunohistochemical expression of MMP-2 in an experimental progression model of oral cancer - Shrestha, B; Subedi, S; Bayracharya, D; Radhakrisnan, R (Journal of Chitwan Medical College, 2014)
The progression from normal to dysplasia to carcinoma involves series of molecular events. Matrix metalloproteinase-2 (MMP-2), proteolytic enzyme causes the degradation of the basement membrane, which is a primary step in cancer invasion and progression. The aim of this study was to compare the expression of MMP-2 in normal mucosa (NOM), oral epithelial dysplasia (OED) and Oral Squamous cell Carcinoma (OSCC).MMP-2 expression was evaluated immunohistochemically in NOM (n = 10), OED in each of its histological grades (n = 26) and OSCC of the lining mucosa (n = 19). A semi quantitative retrospective analysis was carried out in 100 cells in each of 5 different fields at 40x magnification in each case and the proportion of cells expressing MMP-2 were estimated. Suitable positive and negative controls were used for all our analysis. Expression scores of basal cells as well as adjacent stromal cells of OED and tumor cells as well as adjacent stromal cells of OSCC were analyzed. Expression of MMP-2 increased from NOM to OED through different grades to OSCC. Mann Whitney U test for comparison of expression for MMP-2 was statistically significant. However, the comparison for the expression of MMP-2 in mild and moderate dysplasia (p=0.018) as well as moderate and severe dysplasia (p=0.026) was not statistically significant. Increase in the expression of MMP-2 from normal oral mucosa to dysplasia to oral cancer suggests it as an early event in oral carcinogenesis. DOI: http://dx.doi.org/10.3126/jcmc.v4i2.10852 Journal of Chitwan Medical College 2014; 4(2): 3-8